Development of Critical Thinking via Writing and Reading (Journal of Educational Sciences, 2022)
The study is aimed to determine the ability of students to think critically while reading and writing. The teaching methodology included the preparation of texts of reports and their reading by students of the 8th grade to develop writing and reading skills in English, the development of critical thinking.Methods of quantitative analysis, descriptive statistics, survey-test, Student's t-test were used. The study involved a teacher and a researcher (English teacher), 42 eighth graders. To collect data, assessment of educational achievements, analysis of documents and examination (preliminary and post-test) were carried out. The study was carried out in three stages: planning, execution, monitoring and reflection were the main stages of this study. The research base is the Nazarbayev Intellectual School of Physics and Mathematics in Shymkent.In addition to the results of observation, according to the results of the assessment test, it was found that the average score of students increased from 43.71 on the results of the preliminary test to 74.45 on the results of the final test. The effectiveness of the methodology for the development of critical thinking according to the Student's t-criterion is shown. The use of the methodology also had a positive impact on the target audience (students and teachers), and also increased the pedagogical and professional competence of teachers in developing, planning and conducting lessons aimed at developing critical thinking. Key words:productive skills, quantitative statistics, research, receptive skills, analyses, creativity, expressing ideas, mental growth.